Answer:
B
Step-by-step explanation:
The cube of twice a number =
Decreased by 11 =
Hence, the cube of twice a number decreased by 11 =
Answer:
x=3
Step-by-step explanation:
<em>3</em><em>x</em><em>-</em><em>4</em><em>=</em><em>8</em><em>-</em><em>x</em><em>(</em><em>Group</em><em> </em><em>like</em><em> </em><em>terms</em><em>)</em>
<em>3</em><em>x</em><em>+</em><em>x</em><em>=</em><em>8</em><em>+</em><em>4</em><em>(</em><em>Add</em><em> </em><em>both</em><em> </em><em>sides</em><em>)</em>
<em>4</em><em>x</em><em>=</em><em>1</em><em>2</em><em>(</em><em>After</em><em> </em><em>adding</em><em> </em><em>you</em><em> </em><em>will</em><em> </em><em>proceed </em><em>to</em><em> </em><em>divide</em><em> </em><em>both</em><em> </em><em>sides</em><em> </em><em>by</em><em> </em><em>4</em><em>)</em>
<em>x</em><em>=</em><em>3</em><em>(</em><em>x</em><em> </em><em>is</em><em> </em><em>3</em><em> </em><em>because</em><em> </em><em>4</em><em> </em><em>can</em><em> </em><em>divide</em><em> </em><em>1</em><em>2</em><em> </em><em>3</em><em> </em><em>times</em><em> </em><em>that's</em><em> </em><em>why</em><em> </em><em>we</em><em> </em><em>have</em><em> </em><em>x</em><em> </em><em>as</em><em> </em><em>equal</em><em> </em><em>to</em><em> </em><em>3</em><em>)</em>
The equation factors as
.. (x +3)(x +4) = 0
By the zero-product rule, the roots are
.. x1 = -4
.. x2 = -3